Syntactic Freezing as Semantic Matching: Licensing Syntactic Deviation in Echo Questions - Ji, Jing (Proceedings of the Amsterdam Colloquium, 2025)
Echo questions (EQs) with an interrogative base have been regarded as syntactically more constrained than declarative-based EQs by involving a frozen CP structure (Sobin, 2010). This paper argues against syntactic freezing and claims that both declarative and interrogative-based EQs are uniformly licensed by entailment defined over information content. The seemingly freezing effect of EQs arises despite entailment when relevant domain alternatives of the antecedent are factored into calculating the meaning of the base such that strict entailment is blocked by exhaustivity inference.